Numerical analysis for interphase forces of gas-liquid flow in a multiphase pump. Issue 6 (15th October 2018) - Liu, Ming; Cao, Shan; Cao, Shuliang
Abstract : Purpose: The modeling of interphase forces plays a significant role in the numerical simulation of gas–liquid flow in a rotodynamic multiphase pump, which deserves detailed study. Design/methodology/approach: Numerical analysis is conducted to estimate the influence of interphase forces, including drag force, lift force, virtual mass force, wall lubrication force and turbulent dispersion force. Findings: The results show that the magnitude of the interphase forces can be sorted by: drag force > virtual mass force > lift force > turbulent dispersion force > wall lubrication force. The relations between interphase forces and velocity difference of gas–liquid flow and also the interphase forces and gas volume fraction are revealed. The distribution characteristics of interphase forces in the passages from impeller inlet to diffuser outlet are illustrated and analyzed. According to the results, apart from the drag force, the virtual mass force, lift force and turbulent dispersion force are required, whereas wall lubrication force can be neglected for numerical simulation of gas–liquid flow in a rotodynamic multiphase pump. Compared with the conventional numerical method which considers drag force only, the relative errors of predicted pressure rise and efficiency based on the proposed numerical method in account of four major forces can be reduced by 4.95 per cent and 3.00 per cent, respectively. Originality value: The numerical analysis reveals the magnitude and distribution of interphase forces inside multiphase pump, which is meaningful for the simulation and design of multiphase pump.